Thyristor Voltage Regulators of the Transformer for Distribution Networks - et. al., Michael G. Astashev, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Features of output voltage regulation of power transformers for distribution networks are presented. The approach to implementation of thyristor voltage regulators for on-load mass-produced power transformers is presented. Examples of circuit solutions for creating thyristor voltage regulators are given. Adaptive control algorithms of thyristor voltage regulators are described. Basic requirements for the control system are submitted. MATLAB simulation results are presented. Physical models are developed and experimental results are described.